Analysis of Fc-dependent effector functions of anti-malaria circumsporozoite protein antibodies - Stefanutti, Erin; Ramani, Rashmi; Whitener, Bradley; Dang, Ha; Bélanger, Simon; Somasundaram, Logeshwaran; Cortina, Karen; De Marco, Anna; Tam, Tommy; Chai, Qingqing; Cameroni, Elisabetta; Gupta, Rajesh; et al. (Microbiology spectrum, 2025)
Malaria disease imposes a major burden on global health, causing over half a million annual deaths. Recent clinical trials in humans have shown that therapeutic antibodies can provide prophylactic protection against malaria in target populations. However, the cost of goods for therapeutic antibodies is high, and the malaria disease burden is concentrated in resource-challenged regions. Engineering the antibody Fc domain to more efficiently engage the immune system is an appealing strategy to increase the potency of therapeutic antibodies but has been minimally tested for malaria. Here, we present evidence that the Fc domain of malaria therapeutic antibodies can confer protection in animal models and can be engineered for more potent stimulation of diverse parasite-targeting immune responses.